Determining Student Achievement Using the Weighted Sum Model Method Based on the Decision Support System - Rizal Furqan Ramadhan (Informatics and Software Engineering, 2025)
The field of education has a strong influence on the state and nation. A good education will produce good products for the country's future development. The foundation of a country is a good education system that produces high-quality alumni. The educational institution in question is a university. Universities can produce graduates of varying quality. This will cause a few problems in the development of education in Indonesia. The importance of student quality in a tertiary institution underscores the need for systematic, measurable assessment. Assessment of outstanding students can be grouped into 2 criteria: academic-based and non-academic-based. The assessment of undergraduate students refers to the selection guidelines for outstanding undergraduates issued by the Ministry of Research, Technology, and Higher Education. A computerized system is needed to store large amounts of data to support student selection (assessment) activities, enabling them to be carried out effectively and efficiently. The Decision Support System is one of the information system models that can implement this idea. The basic concept of a Decision Support System is to provide decision recommendations to the manager or leader of a case. The system's output produces the 5 best students with the highest score of 4.4. Assessment of outstanding students using the Decision Support System is more effective and reduces mathematical calculation errors in the assessment process. A computerized Decision Support System can store large amounts of data and process large volumes.